URGENSI SIDIK JARI PENGHADAP PADA MINUTA AKTA BERDASARKAN PASAL 16 AYAT (1) HURUF C UNDANG-UNDANG NOMOR 2TAHUN 2014 TENTANG PERUBAHAN ATAS UNDANG-UNDANG NOMOR 30 TAHUN 2004TENTANG JABATAN NOTARIS - , GERNALIA NOVA P ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study is aimed to assess the urgency of the obligation of the attachment of appearerâs finger prints and its implementation on the minute as well as to examinethe legal effect of the minute without fingerprints based on the Article 16 paragraph (1) letter C Act Number 2 Year 2014. This research is a normative empirical research using secondary data and primary data through library research and fieldwork. The secondary data were obtained from primary legal materials, secondary legal materials and tertiary legal materials. Fieldwork was conducte in Sleman employing Chairman of the Regional Advisor Council of Sleman, Chairmanof Regional Supervisor of Indonesian Notary Association in Sleman, and five notaries in the districts of Sleman. Secondary data were obtained from documentation method by using documents as the research instrument, while the primary data were taken from interviews by applying a structural interview guide. The data were analyzed qualitatively and presented descriptively. The results showed that the urgency of fingerprints attached on minute is meant to protect the position of notary and reduce the negation of the deedbythe appearers. The fingerprints are affixed to these separated sheets for each appearer including appeareâsright-hand thumbprint which then will be attached to the minute. Fingerprint on the minute is the confidant of appearerâs signature, and the absence of it does not affect the authenticity of adeed. Based on the results, it is concluded that the absence of appearerâs right-hand thumbprint on a deeddoes not affect the authenticity of the deed. However, fingerprint attachment is used to proveand protect professionalism of Notary. Therefore, notary is suggested too bey the Act of Notary as well as Notary Ethics, while the government should form the rule of implementation of Act Number 2 Year 2014. Keywords : Fingerprint, Notarial Deed, Notary